Student Perceptions of ChatGPT Integration in the Digital Age - Ruyat, Ruyat; Jatiwahyuni, Lucia; Suroso, Jarot S (STMIK Widya Cipta Dharma, 2024)
The digital era presents new opportunities in education, including the integration of artificial intelligence (AI) technologies like ChatGPT. This study explores students' perceptions of using ChatGPT in face-to-face learning through a literature review approach. The analysis draws on various reliable sources, including scientific journals, books, and relevant research reports. The findings suggest that ChatGPT is beneficial for helping students understand materials, complete tasks, and enhance their learning motivation. Additionally, it is considered user-friendly due to its simple interface and quick response times. However, several challenges were identified, including limited digital literacy, the risk of receiving inaccurate information, and the potential misuse of the tool as a shortcut, bypassing deeper engagement with learning materials. The study concludes that ChatGPT holds significant potential to support face-to-face learning, especially when used responsibly under teacher guidance. To maximize its effectiveness, efforts should focus on improving students' digital literacy, establishing clear usage policies, and providing structured guidance during the learning process.